Transcriptome analysis of 'Sijihua' longan (Dimocarpus longan L.) based on next-generation sequencing technology. Issue 2 (3rd March 2016) - Zhang, H. N.; Shi, S. Y.; Li, W. C.; Shu, B.; Liu, L. Q.; Xie, J. H.; Wei, Y. Z.
ABSTRACT: 'Sijihua' longan ( Dimocarpus longan Lour.) blossoms throughout the year, and hence it is a useful material for studies on the mechanism of flowering. However, few genomic resources such as DNA sequences or markers are currently available for 'Sijihua' longan. To increase our understanding of the genetic control of important flowering characteristics in 'Sijihua' longan, we constructed a mixed cDNA library of 'Sijihua' longan using Illumina paired-end sequencing technology and obtained a total of 90, 069, 246 high-quality reads. Among the unigenes, 43.16% (59, 588) had at least one BLASTX hit against the Arabidopsis thaliana sequence database and 42.83% (59, 130) had significant similarity with proteins in the NCBI non-redundant protein database. Of these annotated unigenes, a total of 15, 956 (11.56%) were mapped onto 271 pathways using the Kyoto Encyclopedia of Genes and Genomes Pathway database. Furthermore, 11, 402 unigenes were converted into 13, 236 potential simple sequence repeats (SSRs). Dinucleotide SSRs were the dominant repeat motif, with a frequency of 54.3%, followed by trinucleotide (34.6%) and tetranucleotide (4.7%) repeat motifs. AG/CT repeats (46.29%) were the most frequent motifs in the data set. We focused on gene discovery in the area of regulation of flowering, and transcripts were identified for almost every gene involved in the control of flowering. This study demonstrates that Illumina sequencing technology is a rapid and informative approach to gene discovery and molecular marker development in non-model organisms without a whole genome database. Our results provide a comprehensive sequence resource for investigating the mechanisms of flowering in 'Sijihua' longan, and will establish a platform for further studies on longan.